Participant attributions for global change ratings in unexplained chronic fatigue and chronic fatigue syndrome. (May 2016) - Friedberg, Fred; Coronel, Janna; Seva, Viktoria; Adamowicz, Jenna L; Napoli, Anthony
The purpose of this mixed methods study was to identify participants' attributions for their global impression of change ratings in a behavioral intervention for unexplained chronic fatigue and chronic fatigue syndrome. At 3-month follow-up, participants ( N = 67) were asked "Why do you think you are (improved, unchanged, worse)?" Improved patients pointed to specific behavioral changes, unchanged patients referred to a lack of change in lifestyle, and worsened patients invoked stress and/or specific life events. Identifying patient perceptions of behaviors associated with patient global impression of change–rated improvement and non-improvement may assist in developing more effective management strategies in clinical care.